2019
DOI: 10.1111/iej.13093
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory potential of monospecies biofilm matrix components

Abstract: Aim To assess the inflammatory potential of biofilm matrix constituents of Enterococcus faecalis and Pseudomonas aeruginosa monospecies biofilms on macrophages. Methodology In vitro biofilms of E. faecalis and P. aeruginosa were grown (7 days) in aerobic and anaerobic conditions. The biofilm matrix components: exopolysaccharides (EPS) and extracellular DNA (eDNA) were extracted and quantified. The inflammatory potential of EPS and eDNA was assessed on macrophage cell lines (RAW 267.4) using nitric oxide (NO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Many microorganisms release eDNA within their biofilm matrix. Moreover, eDNA was reported as a component of the EPS matrix of numerous Gram-negative and Gram-positive bacteria ( Ibáñez de Aldecoa et al 2017 ; Ramirez et al 2019 ). However, as far as it is known, there is no information about the eDNA of Geobacillus strain.…”
Section: Discussionmentioning
confidence: 99%
“…Many microorganisms release eDNA within their biofilm matrix. Moreover, eDNA was reported as a component of the EPS matrix of numerous Gram-negative and Gram-positive bacteria ( Ibáñez de Aldecoa et al 2017 ; Ramirez et al 2019 ). However, as far as it is known, there is no information about the eDNA of Geobacillus strain.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro co-culture of P. aeruginosa biofilm matrix exopolysaccharides (EPS) and extracellular DNA (eDNA) with RAW264.7 cells induced a lower-grade inflammatory response than that induced by planktonic bacteria-or LPS-treated cells (Ramirez et al, 2019). In accordance with these reports, we have demonstrated that compared to planktonic bacteria, P. aeruginosa biofilms impaired the production of proinflammatory cytokines, as well as iNOS, while promoting the expression of the anti-inflammatory enzyme, Arg1, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic P. aeruginosa biofilm infections in cystic fibrosis patients are dominated by a Th2 response with increased and decreased levels of IL4 and IFNγ, respectively ( Moser et al, 2000 ; Hartl et al, 2006 ), suggesting that P. aeruginosa biofilms persist by reducing host proinflammatory responses to infection. In vitro co-culture of P. aeruginosa biofilm matrix exopolysaccharides (EPS) and extracellular DNA (eDNA) with RAW264.7 cells induced a lower-grade inflammatory response than that induced by planktonic bacteria‐ or LPS-treated cells ( Ramirez et al, 2019 ). In accordance with these reports, we have demonstrated that compared to planktonic bacteria, P. aeruginosa biofilms impaired the production of proinflammatory cytokines, as well as iNOS, while promoting the expression of the anti-inflammatory enzyme, Arg1, both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted March 15, 2021. ; https://doi.org/10.1101/2021.03.15.435450 doi: bioRxiv preprint 7 Deionized water (20 µl), 5% phenol solution (20 µl) (Sigma Aldrich, St. Louis, MO, USA) and 98% sulfuric acid (100 µl) were added to the wells and incubated at 90°C for 30 min [41]. The absorbance was measured at 492 nm using a microplate reader, and the concentration of biofilm exopolysaccharides was determined using a standard curve generated using glucose standards.…”
Section: Quantification Of Biofilm Exopolysaccharidesmentioning
confidence: 99%